Degradable sugar-based magnetic hybrid nanoparticles for recovery of crude oil from aqueous environments. Issue 30 (18th February 2020) - Dong, Mei; Song, Yue; Wang, Hai; Su, Lu; Shen, Yidan; Tran, David K.; Letteri, Rachel A.; Flores, Jeniree A.; Lin, Yen-Nan; Li, Jialuo; Wooley, Karen L.
Abstract : We designed and fabricated a sugar-based magnetic nanocomposite material that is capable of tackling environmental pollution posed by marine oil spills, while minimizing potential secondary problems that may occur from microplastic contamination. Abstract : In this work, we designed and fabricated a nanoscopic sugar-based magnetic hybrid material that is capable of tackling environmental pollution posed by marine oil spills, while minimizing potential secondary problems that may occur from microplastic contamination. These readily-defined magnetic nanocomposites were constructed through co-assembly of magnetic iron oxide nanoparticles (MIONs) and a degradable amphiphilic polymer, poly(ethylene glycol)- b -dopamine-functionalized poly(ethyl propargyl glucose carbonate)- b -poly(ethyl glucose carbonate), PEG- b -PGC[(EPC-MPA)- co -(EPC-DOPA)]- b -PGC(EC), driven by supramolecular co-assembly in water with enhanced interactions provided via complexation between dopamine and MIONs. The composite nanoscopic assemblies possessed a pseudo -micellar structure, with MIONs trapped within the polymer framework. The triblock terpolymer was synthesized by sequential ring-opening polymerizations (ROPs) of two glucose-derived carbonate monomers, initiated by a PEG macroinitiator. Dopamine anchoring groups were subsequently installed by first introducing carboxylic acid groups using a thiol–yne click reaction, followed by amidation with dopamine. The resulting amphiphilic triblock terpolymers and MIONs were co-assembled to afford hybrid nanocomposites using solvent exchange processes from organic solvent to water. In combination with hydrophobic interactions, the linkage between dopamine and iron oxide stabilized the overall nanoscopic structure to allow for the establishment of a uniform globular morphology, whereas attempts at co-assembly with the triblock terpolymer precursor, lacking dopamine side chains, failed to afford well-defined nanostructures. The magnetic hybrid nanoparticles demonstrated high oil sorption capacities, ca. 8 times their initial dry weight, attributed, in part, to large surface areas leading to effective contact between the nanomaterials and hydrocarbon pollutants. Moreover, the naturally-derived polymer framework undergoes hydrolytic degradation to break down into byproducts that include glucose, ethanol and dopamine if not recovered after deployment, alleviating concerns of potential microplastic generation and persistence.